Schreibende Professionals – Typologie einer Zielgruppe für Weiterbildungen im beruflichen Schreiben - Stefanie Marek (Hermes)
Professional writing competence is considered a key prerequisite for professional and societal participation across industries. Unlike professional writers in fields such as journalism, technical writing, or public relations, the majority of the approximately 40 million employed individuals in Germany do not receive advanced professional writing training after completing their school and vocational education – yet they are writing professionals. In German writing studies and didactics, this group has been scarcely studied or described, despite an apparent need for training and research. This article presents qualitative and quantitative characteristics of this population group based on an analysis of linguistic literature and demographic statistics, to identify gaps in the existing research. The description of this group serves as a foundation for further research into writing at work and for the development of professional writing pedagogy